2016
DOI: 10.1152/jn.01117.2015
|View full text |Cite
|
Sign up to set email alerts
|

Preferential distribution of nociceptive input to motoneurons with muscle units in the cranial portion of the upper trapezius muscle

Abstract: Dideriksen JL, Holobar A, Falla D. Preferential distribution of nociceptive input to motoneurons with muscle units in the cranial portion of the upper trapezius muscle. J Neurophysiol 116: 611-618, 2016. First published May 25, 2016 doi:10.1152/jn.01117.2015Pain is associated with changes in the neural drive to muscles. For the upper trapezius muscle, surface electromyography (EMG) recordings have indicated that acute noxious stimulation in either the cranial or the caudal region of the muscle leads to a rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 37 publications
3
31
0
Order By: Relevance
“…Interestingly, similar changes in the amplitude distribution within the VM were observed when VL was injected with hypertonic saline, although to a lesser extent and less consistently across participants. This stereotypical redistribution of activation appears to be, in part, consistent with that observed when noxious stimuli were applied to different regions of the upper trapezius [6,7]. The absence of changes in spatial distribution when VMP was injected may be related to the different function of the distal (patellar stabilization) vs. proximal (knee extension) regions of the vasti, although further interpretation of this proposal is beyond the scope of the present investigation.…”
Section: Discussionsupporting
confidence: 84%
“…Interestingly, similar changes in the amplitude distribution within the VM were observed when VL was injected with hypertonic saline, although to a lesser extent and less consistently across participants. This stereotypical redistribution of activation appears to be, in part, consistent with that observed when noxious stimuli were applied to different regions of the upper trapezius [6,7]. The absence of changes in spatial distribution when VMP was injected may be related to the different function of the distal (patellar stabilization) vs. proximal (knee extension) regions of the vasti, although further interpretation of this proposal is beyond the scope of the present investigation.…”
Section: Discussionsupporting
confidence: 84%
“…From this hypothesis, it would be expected to observe uncoordinated motor unit activity and activation given that muscle ber damage has occurred and motor units may be differentially potentiated or sensitized. The ndings from studies inducing acute nociception in the muscle support this hypothesis [22,45].…”
Section: Discussionmentioning
confidence: 71%
“…The Delsys Trigno system, which includes sensors, the Trigno base station, and the EMGworks software will be used to decompose the acquired EMG signals into individual motor units. The following parameters will be analyzed: the ring times and frequency of individual motor units, motor unit action potential amplitude and shapes [40][41][42], the root mean square value (RMS) of each channel and of the entire signal [22], the coe cient of variation for force steadiness [43], and the centroid of the EMG signal in the cranial-caudal and the medial-lateral directions [22]. This will be repeated for each contraction.…”
Section: Semg Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…MU firing rate (Holobar et al 2010) and reflex inhibition/facilitation (Yavuz et al 2015) estimated with this method were shown to be valid when compared to gold-standard intramuscular recordings. To identify the MUs that were active in both conditions, epochs from the recordings during each condition were spliced together and decomposed as a single recording and a procedure based on the spatial representation of the MU action potential (Dideriksen et al 2016) was used to verify the correct matching of MUs. With spike-triggered averaging, the spatial representation of the action potential of each MU was obtained for Free Standing and Lying Supine conditions separately.…”
Section: Methodsmentioning
confidence: 99%